Politainment in the 2024 Indonesian presidential election and positioning in downstream industry - Bismar Harris Satriawan; Anyualatha Haridison; Jhon Retei Alfri Sandi; Dian Iskandar; Purnama Julia Utami; Andi Ilmi Utami Irwan; Nursaleh Hartaman (Frontiers in Political Science)
This research explains how Prabowo Gibran’s politainment strategy and their political positioning on downstream industry issues during the 2024 Indonesian presidential election. It further evaluates voter perceptions of Prabowo-Gibran’s politainment strategy and their political positioning on these issues. This study employed a mixed-method approach using a sequential exploratory strategy model. The qualitative approach was carried out using in-depth interviews and documentation techniques, while the quantitative approach was carried out using a survey method. The results indicate that Prabowo-Gibran’s politainment strategy was highly effective in garnering support and increasing their vote share in the 2024 election. The majority of Prabowo–Gibran voters viewed this strategy positively and highlighted its effectiveness in influencing voter decisions. Additionally, the majority of voters expressed agreement and optimism with Prabowo-Gibran’s political positioning in sustainability policies for the downstream industry. These findings offer valuable insights to candidates and political parties by providing guidance on the effective use of politainment and strategic political positioning to influence final voter decisions in general elections.